A new species of short unpatterned moray eel (Anguilliformes: Muraenidae) from the northwestern Indian Ocean, including the Socotra Archipelago, with a redescription of Gymnothorax pseudoherrei Böhlke - Smith, David G.; Bogorodsky, Sergey V.; Dandar, James; Zajonz, Uwe (Zootaxa, 2024)
A new species of short brown unpatterned moray eel, Gymnothorax. arabicus sp. nov., is described based on specimens collected from the northwestern Indian Ocean, including the Red Sea, Socotra Archipelago, and Arabian Gulf. The new species is characterized by having the dorsal-fin origin before the gill opening, two branchial pores, one or two median intermaxillary teeth, biserial maxillary teeth, total vertebrae 114–120, and a plain brown head and body with dark yellow color at the tip of the tail. The new species formerly has been confused with G. pseudoherrei but is distinguished from it by having slightly more total vertebrae (114–120 vs. 111–116), dark stripes on the throat and side of the head, and a larger maximum size (ca. 300 mm TL vs. ca. 200 mm TL). Gymnothorax pseudoherrei, currently known from the Maldives and Sri Lanka to the Philippines, Solomon Islands, and northern Australia, is redescribed in the present study. A comparison of the COI mtDNA in BOLD, in association with published phylogenetic evidence, confirms that G. arabicus and G. pseudoherrei form two separate genetic lineages, corroborating the morphological data.